Fiscal policy led by tax incentives - Bogovac, Jasna (Naše gospodarstvo, 2014)
Multinational enterprises play an important role in the field of foreign direct investment activity. However, investments that are desirable from the standpoint of the host country might be rejected by the strategic management of multinational enterprises due to other, more important aspects of the tax system, such as tax risks. This paper examines how important tax incentives are for Croatian multinational enterprises as a fiscal instrument for attracting foreign direct investment. We found that tax incentives play an important role during the strategic decision-making process of multinational enterprises, in which the decisive factors are unpredictable tax risks and costs.
Keywords: korporacije; multinacionalne družbe; investicije; tax; davki; davčna politika; Croatia; Hrvaška